Todo fluye - Grossman, Vasiliĭ (Galaxia Gutenberg, 2014)
The novel tells the story of Ivan Grigoryevich, who has returned to Russia after thirty years in the Gulag. After short and unsatisfying visits to familiar places and persons in Moscow and Leningrad, the hero settles in a southern provincial town where he briefly establishes a new life with a war widow. Ivan Grigoryevich eventually returns to his boyhood home on the Black Sea, where he is finally able to come to terms with the inhumanity of the new Russian regime.